RVAR - Cleator,SF; Harrison,SP; Nichols,NK; Prentice,I; Roulstone,I (2020)
Make spatially coherent gridded maps of the palaeoclimate by combining site-based pollen reconstructions and climate model outputs using a conditioned 3D variational data assimilation method.